Health-related Internet Use by Caregivers of Children and Adolescents With Cancer. Issue 2 (9th March 2023) - Harney, Sarah; Chu, Tzu-Chun; Trask, Christine L.; Welch, Jennifer J.G.
Abstract : Caregivers of children with cancer have needs for information and social support related to their child's diagnosis. The internet serves as a resource to help meet these needs. There is growing interest in health-related internet use (HRIU) by caregivers of pediatric patients as the internet rapidly evolves. This survey study describes patterns of internet use by caregivers of children with cancer and examines associations between socioeconomic status and internet use. 114 caregivers participated between 2014 and 2016. The majority (82%) reported frequent general internet use, but fewer (25-54%) reported frequent HRIU. Very few respondents (4%) reported difficulty accessing the internet; those reporting difficulty were more likely to report lower income, public/no insurance, and lower educational attainment. There were no consistent associations between socioeconomic status variables and frequency of HRIU. Less than half (43%) of caregivers reported that their internet use raised questions that they discussed or planned to discuss with the child's nurse or doctor, and only 4% reported having changed medical decisions based on information found on the internet. We conclude that caregivers of children with cancer engage in HRIU, and this is an area for improvement in oncology anticipatory guidance and family-centered care.